AB0422 LEFT VENTRICULAR ABNORMALITIES IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS FOLLOWED BY SEQUENTIAL ECHOCARDIOGRAPHY. (2nd June 2020) - Kuga, T.; Matsushita, M.; Tada, K.; Yamaji, K.; Tamura, N.
Abstract : Background: Cardiovascular disease (CVD) is detected in up to 50% of systemic lupus erythematosus (SLE) patients 1 and major cause of death 2 . Even clinically silent SLE patients can develop left ventricular (LV) diastolic dysfunction 3 . Proper echocardiographic follow up of SLE patients is required. Objectives: To clarify how the prevalence of LV abnormalities changes over follow-up period and identify the associated clinical factors, useful in suspecting LV abnormalities. Methods: 29 SLE patients (24 females and 5 men, mean age 52.8±16.3 years, mean disease duration 17.6±14.5 years) were enrolled. All of them underwent echocardiography as the baseline examination and reexamined over more than a year of follow-up period(mean 1075±480 days) from Jan 2014 to Sep 2019. Patients complicated with pulmonary artery hypertension, deep venous thrombosis or pulmonary embolism and underwent cardiac surgery during the follow-up period were excluded. Left ventricular(LV) systolic dysfunction was defined as ejection fraction (EF) < 50%. LV diastolic dysfunction was defined according to ASE/EACVI guideline 4 . LV dysfunction (LVD) includes one or both of LV systolic dysfunction and LV diastolic function. Monocyte to HDL ratio (MHR) was calculated by dividing monocyte count with HDL-C level. Prevalence of left ventricular abnormalities was analysed at baseline and follow-up examination. Clinical characteristics and laboratory data were compared among patient groups as follows; patients with LV dysfunction (Group A) and without LV dysfunction (Group B) at the follow-up echocardiography, patients with LV asynergy at any point of examination (Group C) and patients free of LV abnormalities during the follow-up period (Group D). Results: At the baseline examination, LV dysfunction (5/29 cases, 13.8%), LV asynergy (6/29 cases, 21.7%) were detected. Pericarditis was detected in 7 patients (24.1%, LVD in 3 patients, LV asynergy in 2 patients) and 2 of them with subacute onset had progressive LV dysfunction, while 5 patients were normal in echocardiography after remission induction therapy for SLE. At the follow-up examination, LV dysfunction (9/29 cases, 31.0%, 5 new-onset and 1 improved case), LV asynergy (6/29 cases, 21.7%, 2 new-onset and 2 improved cases) were detected. Though any significant differences were observed between Group A and Group B at the baseline, platelet count (156.0 vs 207.0, p=0.049) were significantly lower in LV dysfunction group (Group A) at the follow-up examination. Group C patients had significantly higher uric acid (p=0.004), monocyte count (p=0.009), and MHR (p=0.003) than Group D(results in table). Conclusion: LV dysfunction is progressive in most of patients and requires regular follow-up once they developed. Uric acid, monocyte count and MHR are elevated in SLE patients with LV asynergy. Since MHR elevation was reported as useful marker of endothelial dysfunction 5, our future goal is to analyse involvement of monocyte activation and endothelial dysfunction in LV asynergy of SLE patients. References: [1]Doria A et al. Lupus. 2005;14(9):683-6. [2]Manger K et al. Ann Rheum Dis. 2002 Dec;61(12):1065-70. [3]Leone P et al. Clin Exp Med. 2019 Dec 17. [4]Nagueh SF et al. J Am Soc Echocardiogr. 2016 Apr;29(4):277-314. [5]Acikgoz N et al. Angiology. 2018 Jan;69(1):65-70. Numbers are median (interquartile range), Mann-Whitney u test were performed, p value less than 0.05 was considered statistically significant. Disclosure of Interests: None declared